DESIGN, DEVELOPMENT, AND CHARACTERIZATION OF OROMUCOSAL WAFER OF TRAMADOL HYDROCHLORIDE - Wadetwar, Rita N; Charde, Tejaswini (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present work was the preparation of fast-dissolving film of tramadol HCl (TMH) using water-soluble polymer, to achieve faster onset of action, to improve patient compliance, ease of dosing, and bypass the first-pass metabolism. Methods: TMH oromucosal wafers were prepared using pullulan as natural, biodegradable polymer, and propylene glycol as plasticizer by solvent casting method. Formulation batches were prepared using 32 full-factorial designs. The prepared TMH oromucosal wafers were characterized for morphology, uniformity of weight, drug content, folding endurance, in vitro disintegration time (DT), % moisture content, surface pH, in vitro % drug release, ex vivo permeation studies, compatibility studies (differential scanning calorimetry, Fourier transform infrared spectroscopy, and X-ray diffraction), and stability studies. Results: Optimized batch of mouth-dissolving film of TMH containing pullulan as polymer showed 98.67±0.11% drug release at 6 min. It showed better folding endurance 88 No. of folds, in vitro DT 5.11 s, surface pH 6.84±0.12 pH, thickness 0.17±0.11 mm, and percentage content uniformity 98.45±0.48%. Stability studies carried out for the best formulation FDF5 revealed that the formulation was stable. Conclusion: The results obtained in this research work clearly indicated a promising potential of fast-dissolving oral films using natural biodegradable polymer, pullulan which gave rapid drug delivery and rapid onset of action of centrally acting drug, TMH for patients suffering from pain.